ANALISIS VARIASI ANGLE PATTERN FARM TERHADAP KINERJA TURBIN ANGIN DARRIEUS TIPE H MENGGUNAKAN METODE CFD - Reinordt (2024)
The development of renewable energy wind turbines in Indonesia is still lacking, especially wind turbine types vertical. Axis wind turbine vertical Darrieus type is one of the technologies that can be applied in Indonesia because the application is easy and can generate electricity for the community. Therefore the authors conducted research that aims to use wind turbines for the development of wind turbines in Indonesia so that they can be applied as a way to convert renewable energy into electrical energy. To get formation twin good turbine with the application of variations angle pattern farm research was carried out using the CFD method with software ANSYS Fluent. And the author also recommends formations twin the best turbine for wind turbine applications vertical axis darrieus. The results of the conclusions of this study indicate that twin wind turbine darrieus tipe-H with variations angle pattern farm 60º with a distance of 1 Diameter at TSR 2.5 has a sufficient increase in the efficiency of the power coefficient (Cp)significant. The increase in power efficiency (Cp) which was previously obtained by a single turbine, namely 0.307 to 0.344 by twin turbine using variations angle pattern farm 60º with a distance of 1 Diameter with a percentage increase in efficiency of about 12%. This can happen because in this study researched and used the help of wind from turbine 1 exhaust as wind power assistance to turbine 2 so that turbine 2 gets a better power coefficient (Cp). So that after being averaged we get a better power coefficient (Cp) compared to single turbine.